First Record of Pleurocrypta petrolisthis Markham, 1988 (Isopoda, Bopyridae) Parasitizing a Porcelain Crab (Porcellanidae) from Brazil, with Notes on Morphology and Ecology - Horch, Amanda P.; Nogueira, Caio Santos [UNESP]; Santos, Rafael Carvalho [UNESP]; Guéron, Rodrigo; Pasinatto, Karmine; Costa, Rogerio Caetano [UNESP]; Moraes, Isabela R. R. (Springer Nature, 2025)
PurposeIsopods of the genus Pleurocrypta Hesse, 1865 are branchial parasites of squat lobsters and porcelain crabs. Here, we record Ple. petrolisthis Markham, 1988 from Brazil for the first time, infesting the porcelain crab Petrolisthes galathinus (Bosc, 1801), and provide new morphological and ecological data.MethodsSamplings were conducted in Pernambuco and São Paulo, Brazil, between 2021 and 2022, using active and passive methods. Illustrations of Ple. petrolisthis were made with a drawing tube mounted on a stereomicroscope and a compound microscope, then traced using Adobe Illustrator. Statistical analyses were conducted on prevalence, side preference and the relationship between parasite and host size.ResultsSpecimens conform well with the original description of Ple. petrolisthis, with few morphological differences in the females. In the males, the segmentation of pleon varied from fully fused to five-segmented, and the maxillipeds are present. Prevalence is higher than for other species of Pleurocrypta, and no preference for side of the branchial chamber was observed. Parasite size influenced host size, probably due to the deformation of the carapace in infested hosts.ConclusionThe study expands the distribution of Ple. petrolisthis from its type locality in Bonaire to Brazil. The variation in the pleon segmentation of the males is described for the first time, and the presence of maxillipeds is added to the original description. This is the first study to provide ecological data for any of the Western Atlantic species of Pleurocrypta, widening our knowledge of the relationship between bopyrids and their hosts.